"Dissolution-Capture" Strategy to Form Monodispersed Nitrogen-Doped Hollow Mesoporous Carbon Spheres. Issue 14 (1st January 2016) - Chen, Aibing; Xia, Kechan; Yu, Yifeng; Sun, Hexu; Liu, Lei; Ren, Shaofeng; Li, Yuetong
Abstract : Monodispersed nitrogen-doped hollow mesoporous carbon spheres (N-HMCSs) have been successfully synthesized using a novel "dissolution-capture" method. The mesoporous silica is uniformly coated on the surface of the polystyrene/polyacrylonitrile composite nanospheres (PS@PAN) core by using a modified Stöber method. Then a hollow cavity is formed through the dissolution of the PS@PAN in organic solvent. The dissolved PS@PAN as the carbon and nitrogen precursor is captured in the mesochannels of the silica shell. The obtained N-HMCSs have high specific surface area of 807 m 2 g −1, uniform mesopore size of 4.1 nm, and nitrogen content of 3.6 at.%. In addition, the N-HMCSs show a high specific capacitance of 212 F g −1 at a current density of 1 A g −1 in 6 M KOH electrolyte and capacitance retention of 93.9% after 10000 charge/discharge cycles at 5 A g −1 . The "dissolution-capture" method can give a useful enlightenment for the design of electrode materials for supercapacitors.